Español - Español; Español (Ars Pharmaceutica (Internet), 1969)
A gravimetric and complexometric technics of evaluation of "bismuth subgalate" has been newly revised. We recommanded a complexometric technic using EDTA and Pyrocatechol Viol or Thiourea as indicator indiferently in order to include it in the new Spanich Pharmacopoeia edition